Nilai-Nilai Pendidikan Geopolitik Islam dan Kepemimpinan Islam pada Sejarah Muhammad Al-Fatih - Ardianti, Cut Putri Qory; Paramansyah, Arman; Suryana, Agus (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The issue of leadership has become a significant polemic, burdening the functioning of all state affairs. Moreover, Indonesia, with its substantial geopolitical potential, aspires to become a major maritime power, in line with its status as the world's largest Muslim-majority country. This study aims to examine the values of Islamic geopolitical education and Islamic leadership as demonstrated in the history of Muhammad Al-Fatih. The research is conducted using a descriptive qualitative method, with data sources gathered from Islamic historical and geopolitical literature. The findings reveal that Muhammad Al-Fatih integrated Islamic geopolitical education into his transformational leadership. Al-Fatih not only had a clear vision of Islamic territorial expansion but also implemented innovative strategies based on a deep understanding of Islamic geopolitics. His leadership also balanced spiritual and worldly aspects, with Islamic creed principles incorporated into his leadership policies. These findings provide significant insights into how Islamic geopolitical education can be applied in modern leadership contexts to produce leaders of integrity and broad vision.